Jmjd3 Negatively Regulates Reprogramming Through Histone Demethylase Activity- Dependent and -Independent Pathways - Zhao, Wei (2013)
Although somatic cell reprogramming to generate inducible pluripotent stem cells (iPSCs) is associated with profound epigenetic changes, the roles and mechanisms of epigenetic factors in this process remain poorly understood. Here we identify Jmjd3 as a potent negative regulator of reprogramming. Jmjd3-deficient MEFs produced significantly more iPSC colonies than did wild-type cells, while ectopic expression of Jmjd3 markedly inhibited reprogramming. We show that the inhibitory effects of Jmjd3 are produced through both histone demethylase-dependent and -independent pathways. The latter pathway is entirely novel and involves Jmjd3 targeting of PHF20 for ubiquitination and degradation via recruitment of an E3 ligase, Trim26. Importantly, PHF20-deficient MEFs could not be converted to fully reprogrammed iPSCs, even with knockdown of Jmjd3, Ink4a or p21, indicating that this protein exerts predominant effects on reprogramming. Our findings demonstrate a previously unrecognized role of Jmjd3 in cellular reprogramming and provide molecular insight into the mechanisms by which the Jmjd3-PHF20 axis controls this process.